Thromboembolic risk after lumbar spine surgery: a cohort study on 325 000 French patients. (10th July 2018) - Bouyer, B.; Rudnichi, A.; Dray‐Spira, R.; Zureik, M.; Coste, J.
Abstract : Essentials The risk of venous thromboembolism (VTE) after lumbar spine surgery (LBS) is not precisely known. More than 320 000 patients who underwent LBS in France between 2009 and 2014 were followed‐up. The overall risk of VTE after LBS is less than 1% but modulated by patient and procedural factors. Surgical device implantation, anterior approach and complex surgery increase the risk of VTE. Summary: Background: Postoperative venous thromboembolism (VTE) is a severe complication, the risk of which after lumbar spine surgery (LBS) is not precisely known. Objective: To estimate the incidence of VTE after LBS, and to identify individual and surgical risk factors. Methods: All patients aged >18 years who underwent LBS in France between 2009 and 2014 were identified. Among 477 024 patients screened, exclusions concerned recent VTE or surgery, and multiple surgeries during the same hospital stay. Results: In 323 737 patients (mean age 52.9 years, 51.4% male), we observed 2911 events (0.91%) after a median time of 12 days (Q1–Q3: 5–72 days). The multivariate adjusted Cox model showed increased risks associated with age (4% per year of age; 95% confidence interval [CI] 3.8–4.3), obesity (hazard ratio [HR] 1.32, 95% CI 1.18–1.46), active cancer (HR 1.65, 95% CI 1.5–1.82), previous thromboembolism (HR 5.41, 95% CI 4.74–6.17), severe paralysis (HR 1.47, 95% CI 1.17–1.84), renal disease (HR 1.28, 95% CI 1.04–1.6), psychiatric disease (HR 1.21, 95% CI 1.1–1.32), use of antidepressants (HR 1.13, 95% CI 1.03–1.24), use of contraceptives (HR 1.56, 95% CI 1.19–2.03), extended surgery for scoliosis (HR 3.61, 95% CI 2.96–4.4), implantation of pedicular screws with a 'dose–effect' association, and an anterior approach (HR 1.97, 95% CI 1.6–2.43) or a combined approach (HR 2.03, 95% CI 1.44–2.84). Conclusions: The overall VTE risk after LBS is moderate (< 1%) but is widely modulated by several easily identifiable risk factors. The surgical community should be aware of this heterogeneity, adapt prevention according to patients and to the procedure, and use drug prophylaxis in the event of a high risk being present.